A Qualitative Study to Explore Ways to Observe Results of Engaging Activities in Clients with Dementia - Masahiro Ogawa; Seiji Nishida; Haruna Shirai (Hindawi-Wiley, 2017)
Background. Many occupational therapists face the challenge of helping clients with dementia to select and perform meaningful occupations, which may be difficult due to cognitive impairment. Understanding tacit knowledge of well-experienced occupational therapists could positively affect occupational therapy practice for clients with dementia. Objectives of Study. To explore the observations of experienced occupational therapists when evaluating the effects of activities in clients with dementia. Methods. Ten occupational therapists with over 10 years of clinical experience participated in this qualitative study. In-depth interviews were conducted to ask the question, "What do you observe in clients with dementia when you assess the effectiveness of activities among these clients?" Findings. From 47 cases, we found five major themes and 18 subthemes. Main themes were "engaging activity," "emotional expression during activity," "verbal expression during activity," "social interaction through activity," and "something obtained as outcome of activity." Relevance to Clinical Practice. The 18 subthemes could be used as viewpoints to observe engagements of activity in clients with dementia. Limitations and Recommendations for Further Research. Future studies could examine which viewpoints were utilized for each type of activity and/or severity of dementia as this was not investigated in the current study.